Globalization and the Transformation of Political Attitude Structures at the Party Level in the Arab World: Insights from the Cases of Egypt and Jordan - Malek Abduljaber; Ilker Kalin (Societies, 2019)
In this paper, the outline, design, and findings of an ongoing research project on the effects of globalization on the transformation of political ideology in the Arab world at the political party level are presented. It is argued that globalization has altered the dimensionality, type, and structuration of political ideology in the Arab world. The structure of preferences among political actors in the region shifted from a unidimensional one in the post-independence era to become multidimensional in the contemporary period, defined by high rates of economic, cultural, and political globalization. Arab political parties no longer organize their platforms based on the Islamic–liberal, Islamist–secular, or cultural divides. An economic values-based dimension has emerged to divide party programs, adding a second, distinct and statistically independent dimension to the already existing classic church versus state cleavage. Further, a new family of Islamist parties has emerged due to the economic, cultural, and political gains from globalization. This project argues that globalization causes political ideological shifts in attitudes through formulating new groups, schedules of preferences, and political/economic opportunities. This research contributes to the ongoing debate on the influence of globalization and any other social transformation process on changing political actors’ preferences across time and space.